Islam liberal & fundamental : sebuah pertarungan wacana - Wahid, Abdurrahman (Yogyakarta : eLSAQ Press, 2005)
Pro and con on liberalism in Islam in Indonesia
Keywords: Islam -- Indonesia; Islam -- 20th century -- Indonesia